Comparison of fracture resistance of teeth with prepared protaper next, protaper gold, and hyflex CM rotary files - Rinastiti, Margareta; Widyastuti, Andina; Hadriyanto, Wignyo (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Preparation of the root canal system is a crucial step in root canal treatment. Endodontically treated teeth differ structurally from healthy, untreated teeth. This can lead to root cracking by creating pressure on the canal wall, reducing the fracture resistance of the tooth. Different designs, including cross-sectional shape, tip, taper, flute, radial land, helix angle, rake angle, and pitch, can influence the outcome of the root canal preparation and the risk of root fracture. The purpose of this study was to evaluate the fracture resistance of teeth after root canal preparation using three different NiTi rotary files: ProTaper Next (PN), ProTaper Gold (PG), and HyFlex CM (HC). Thirty premolars with a single and straight root canal were decoronated at the cementoenamel junction, leaving 14 mm of the root. The subjects were divided into 3 groups. Group 1 (n = 10) was prepared using PN, group 2 (n = 10) was prepared using PG, and group 3 (n = 10) was prepared using HC. After instrumentation and irrigation, the specimens were subjected to a continuous vertical compressive force (crosshead-speed of 2.28 mm/sec) in order to record the force (in newtons) until root fracture. To describe the surface characteristic of the dentinal root after the preparation, a section fragment from the apical third of the specimens was observed using a scanning electron microscope (SEM) at 2500x magnification. The micrographs were analyzed according to the Hulsman’s method. The results demonstrated that there was a statistically significant difference in root fracture resistance among the three groups. (p = 0.043). The LSD post hoc test indicated that HC showed a higher root fracture resistance (p < 0.05) compared to both PN and PG. In conclusion, the different file systems of PN, PG, and HC instruments generate different root fracture resistance of teeth. In comparison to PN and PG, HC instruments tend to result in increased fracture resistance.